IMPLEMENTASI â€œGOOD FAITHâ€ PADA PERJANJIAN KERJASAMA ANTARA PERUSAHAAN BEDA NEGARA - Cahyaningtyas, Kartika; Wibowo, Eko Ari (LPPM institut Teknologi Bisnis AAS Indonesia, 2023)
This research examines and analyzes international contracts that do not fulfill the principle of good faith or in Indonesian means Good Faith because the agreement made by the parties is not reached, then there can be disputes between the parties who made the agreement and there could be parties who suffer losses if it arises. the dispute. The legal remedies chosen by the parties making the agreement must be stated in the contents of the agreement. The method used in normative research with a problem approach is the case approach. The research results in the form of Cooperation Agreements between companies from different countries have not implemented the principle of